Building Competitive Firms : Incentives and Capabilities. - Nabi, Ijaz; Luthria, Manjula (Directions in development (Washington, D.C.), 2002)
Building Competitive Firms: Incentives and Capabilities presents a framework that emphasizes the economic and policy incentives needed to create competitive firms and national economies. It also identifies and explains the key capabilities that firms must develop in-house in order to become more competitive. The framework provides a link between important policy issues such as corporate governance, foreign direct investment, innovation readiness, intellectual property rights, e-commerce, skills training and upgrades, and supply chain management. These so called 'behind-the-border' issues are pivotal to improving the national investment climate and increasing the gains from trade liberalization. Contributors to this volume emphasize that while individual firms must take the lead in enhancing competitiveness, the role of public policy remains vital. Efforts by corporate management to increase productivity benefit considerably from government policies that redress market failures and information asymmetries.